Interdisciplinary approach to technical education - KROTKÝ, JAN; KORYTÁŘ, JINDŘICH; SIMBARTL, PETR (Journal of Education, Technology and Computer Science, 2016)
The authors introduce a realistic concept of innovation in teaching technical subjects at primary schools with regard to sustainable development of industrial society. The concept is based on the published results of an institutional survey carried within six organizations which are concerned with teaching the educational area of Man and the World of Work and preparing teachers for the area. The survey was conducted as a part of the project Erasmus +Activity 1, action strategic partnerships for school education no. 2015-1-SK01-KA201-008942 and as a training of the institute of informal way of teaching at Techmania Technology Center. The innovation is seen especially in interdisciplinary connections between subjects, implementation of new modern technologies in teaching and support of informal education.